Fast facts : religion and medicine - Boyle, Deborah C. M. (Fast facts., 2008)
Religion is fundamental to the lives of many patients. "Fast Facts: Religion and Medicine" summarizes the religious practices of the world's most popular faiths and highlights their impact on medical treatment. By having a greater understanding of the religious beliefs and practices of their patients, all healthcare workers can deliver care more sensitively and appropriately. Such consideration will reduce both the physical and emotional stresses imposed by the medical environment, and increase the well-being of patients and their families